Uncatalyzed Formation of Polyaminoboranes from Diisopropylaminoborane and Primary Amines: a Kinetically Controlled Polymerization Reaction. Issue 9 (12th January 2021) - Devillard, Marc; De Albuquerque Pinheiro, Carlos Antonio; Caytan, Elsa; Roiland, Claire; Dinoi, Chiara; Del Rosal, Iker; Alcaraz, Gilles
Abstract: Recently, we disclosed the uncatalyzed formation of polyaminoboranes (PABs) from monomeric diisopropylaminoborane ( i Pr2 N−BH2 ) and primary amines (RNH2 ). Their structure is studied through a detailed multinuclear NMR study and their full spectroscopic characterization is presented revealing that N‐alkyl substituted PABs exhibit magnetically non‐equivalent methylenic protons in the close vicinity of the BN‐backbone. We also performed an in‐depth theoretical study of this global chemical process. The mechanism is fully apprehended and the strong influence of the temperature on the outcome of the reaction is unveiled. DFT‐calculations clearly show that the formation of the polyaminoboranes (RNH−BH2 )n results from a kinetically controlled step‐growth polymerization reaction that can be globally viewed as a head‐to‐tail association process of the in situ generated transient monomeric monoalkylamino‐borane [RNH−BH2 ]. Abstract :